AB0776 The effect of pregnancy on disease activity outcomes in psoriatic arthritis patients. (15th June 2017) - Berman, M; Paran, D; Zisman, D; Wollman, J; Levartovsky, D; Elkayam, O
Abstract : Background: Psoriatic arthritis often affects patients at a childbearing age. The relationship between pregnancy and psoriatic arthritis, in terms of pregnancy outcomes and its effect on disease activity, has not been well studied Objectives: To evaluate the effect of pregnancy on disease activity in psoriatic arthritis Methods: A retrospective review of files of female patients followed at Psoriatic arthritis clinic at the Tel Aviv Medical center was performed, patients with at least 1 pregnancy during follow up and one visit during or soon after pregnancy were included. A review of files was performed which included the following data: age, disease duration, pattern of PsA, disease activity before during and after pregnancy, record of treatment, including IA injections. Postpartum period was defined as up to 1 year after pregnancy. PsA activity was defined as follow: no disease activity (no active synovitis), mild disease (up to 1 joint involved), moderate to severe disease (more than 2 joints involved). The follow-up during and after pregnancy was classified as: improvement, worsening or stable Results: 25 PsA women and 35 pregnancies were identified. 33 resulted in live healthy babies. One pregnancy was interrupted on week 23, so partial follow up was available. The mean age at pregnancy was 32.5 years. Table 1 summarizes status of disease activity before, throughout pregnancy and during the postpartum period in the whole group. No significant change in disease activity was noticed throughout pregnancy while significant proportion of patients flared at postpartum. Before 21 pregnancies patients were treated with biologic agents. In 15, biologic treatment was discontinued close to pregnancy or during the first trimester. In this group, 5 (33%) of patients were classified as mild to severe activity prior to pregnancy. This number increased up to 8 (53%), 7 (47%) and 14 (93%) during the 1st, 2nd trimester and postpartum period respectively. In 6 patients in whom biologics were continued beyond first trimester, no significant change in degree of disease activity was noticed. Interestingly, in the group of non-biologics treated patients, an improvement in disease activity was observed – the proportion of patients with mild to severe disease activity decreased from 85% close to pregnancy to 69% in the 1st and 2nd trimester and 58% in the 3rd one while an increase to 83% was observed after pregnancy. During 6 pregnancies, corticosteroids were initiated or the dosage increased- 83% in pregnancies where biologics were stopped before pregnancy. Conclusions: Patients with PsA definitively flare after pregnancy. Our results suggest that stopping treatment with biologic agents before pregnancy is associated with flare during pregnancy and the postpartum period. It seems that in terms of PsA disease activity, it may be recommended to continue treatment with biologic agents throughout pregnancy Disclosure of Interest: None declared